Computer-assisted audit techniques: classification and implementation by auditor - Serpeninova, Yuliya; Makarenko, Serhii; Litvinova, Marina (Public Policy and Accounting, 2020)
The article deals with the main issues in classification of information technology (IT) in auditing and computer-assisted audit techniques (CAATs) adoption by the auditors during audit process organization. Among these issues, authors underline CAATs adoption, which varied by firm size. There is a strict connection between auditor’s firm size and degree of technologies advances. The most used types of CAATs and IT were generalized, they are: audit software, Electronic Spreadsheets, Electronic Working Papers. Besides these technologies, auditors can often use a program language to gain access to data and manipulate this data. Utility software and specialized audit software (Statistical Software, Test Data, Database SQL Search, Parallel Simulation Software, Embedded Audit Modules) is highly used to perform specific auditor task or facilitate solving a set of audit function performing. To increase audit technology acceptance among audit companies, the technological, organizational and environmental aspects that influence the adoption need to be improved.